2010
DOI: 10.1167/10.9.1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of light transformations and concomitant changes in surface albedo

Abstract: We report two experiments demonstrating that (1) observers are sensitive to information about changes in the light field not captured by local scene statistics and that (2) they can use this information to enhance detection of changes in surface albedo. Observers viewed scenes consisting of matte surfaces at many orientations illuminated by a collimated light source. All surfaces were achromatic, all lights neutral. In the first experiment, observers attempted to discriminate small changes in direction of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…1 We varied the implied masses of the colliding objects by manipulating their simulated materials (Experiment 1) and their sizes (Experiments 2 and 3). Research on the visual perception of material appearance (for reviews, see Anderson, 2011;Maloney & Brainard, 2010) has shown that the surface properties of objects, such as texture, reflectance, colour, and so on, provide unique information about the materials of which objects are made. The phenomenon of "material-weight illusion" lends support to the hypothesis that visually perceived material influences both the expected and the haptically perceived masses of objects (Buckingham, Ranger, & Goodale, 2011;Ellis & Lederman, 1999).…”
Section: Collision Events: Specifics Of Our Contributionmentioning
confidence: 99%
“…1 We varied the implied masses of the colliding objects by manipulating their simulated materials (Experiment 1) and their sizes (Experiments 2 and 3). Research on the visual perception of material appearance (for reviews, see Anderson, 2011;Maloney & Brainard, 2010) has shown that the surface properties of objects, such as texture, reflectance, colour, and so on, provide unique information about the materials of which objects are made. The phenomenon of "material-weight illusion" lends support to the hypothesis that visually perceived material influences both the expected and the haptically perceived masses of objects (Buckingham, Ranger, & Goodale, 2011;Ellis & Lederman, 1999).…”
Section: Collision Events: Specifics Of Our Contributionmentioning
confidence: 99%
“…We have shown in previous psychophysical experiments that human observers utilize binocular disparity to correct the shading gradient direction when estimating the illuminant direction (Gerhard & Maloney, 2010). Thus, we included the shape map in our model, which was used to correct the local gradients in concave regions.…”
Section: Shape Map Inputmentioning
confidence: 99%
“…Estimating illuminant direction from first-order directional derivatives of the luminance map is not a novel idea (Knill, 1990;Lee & Rosenfeld, 1985;Pentland, 1982) but correcting the derivatives for the measured local 3D shape information is. Because we have shown in previous psychophysical experiments (Gerhard & Maloney, 2010) and in the experiment reported here that human observers correct for concave regions when judging lighting direction in stereoscopic scenes, we included a concavity correction in the model.…”
Section: Evaluation Of the Modelmentioning
confidence: 99%
See 2 more Smart Citations